RESPONSIVITAS PEMERINTAH KABUPATEN KAMPAR TERHADAP PELAYANAN PENDIDIKAN DI KECAMATAN TAPUNG HULU ( STUDI KASUS: PENGELOLAAN 7 SDN DAN 3 SMPN DI 5 DESA TAHUN 2018-2020 - Dodi Limidi; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
One of the basic government affairs that must be fulfilled by the Regional Government is public services in the field of education. In carrying out government affairs, it is not uncommon for the Regional Government to encounter problems in its implementation. The problem of education services occurs in 10 schools in 5 villages, the management of the ten schools is carried out by Rokan Hulu Regency while the school area is in the administrative area of the Kampar Regency Government. This study aims to determine the responsiveness of the Kampar Regency Government to education services in the Tapung Hulu District and to find out the impact caused by the school management authority that is not in accordance with the regional jurisdiction.               This study used a qualitative approach with descpriptive methods. Then the data collection techniques used were interviews, observation, and documentation. While the data analysis technique is done by collecting information through interviews, data reduction and data presentation.               The results showed that the responsiveness of the Kampar Regency government to education services in the District of Tapung Hulu by coordinating with the central government on educational issues related to the authority of the ten schools, then budgeting for the procurement of furniture for 10 schools in the APBD-P2020, then taking action by the Kampar district government by assigning teachers a teaching honorarium for the tenth school. As for the impact caused by the problems in school management, namely: the existence of two versions of teachers in one school, student guardians' anxiety and confusion regarding the legality of their child's certificate, and the constrained teacher certification process. Keyword : Response to complaints, Satisfication in education service, Impact of school management.